Effect of adrenalectomy and corticosterone substitution on glucose and glycogen metabolism in rat brain - Plaschke, Konstanze; Müller, Dorothea; Hoyer, Siegfried (Journal of neural transmission, 1996)
In non-nervous tissues, glucocorticoids (GCs) counteract the effects of insulin and stimulate gluconeogenesis. The present study was designed to investigate whether or not adrenalectomy (ADX) and glucocorticoid substitution influence the pathway of both glucose and glycogen metabolism in cerebral parietotemporal cortex and hippocampus, and if so how. The activities of respective key enzymes, such as hexokinase (HK), phosphofructokinase (PFK), pyruvate kinase (PK), glucose-6-phosphatase (G6Pase) and phosphorylase a (PLa), and the concentrations of the intermediates, such as glucose (Glu), glucose-6-phosphate (G6P), fructose-6-phosphate (F6P), fructose-1,6-bisphosphate (F16PP), pyruvate (Pyr), lactate (Lac), glycogen (Glyc) and glucose-1-phosphate (G1F), were measured in the brains of 1-year-old male Wistar rats under controlled conditions 3 days after ADX or sham operation and in a pilot study after ADX and substitution with corticosterone (CST) suspended in sesame oil or after ADX and subcutaneous administration of the vehicle only. An increase in both glycolytic flux and glycogen breakdown and a decrease in gluconeogenesis in cerebral cortex but not in hippocampus were observed after ADX. After substitution with CST in adrenalectomized rats the effect of ADX on enzyme activities was reversed: significant differences from adrenalectomized rats that received vehicle only was shown for PK and G6Pase activities in both areas of the rat brain investigated.